Pengaruh Karakteristik Direktur Utama dan Komite Audit terhadap Manajemen Laba pada Perusahaan Terafiliasi - Melisa Aprillia Dompas; Ceicilia Bintang Hari Yudhanti (Syntax Corporation Indonesia, 2024)
This study aims to determine the effect of the age of the president director, the gender of the president director, the tenure of the president director, and the number of audit committees on profit management. The population of this study is affiliated companies in the manufacturing sector listed on the Indonesia Stock Exchange 2019-2021. The retrieval technique used was purposive sampling and obtained 48 companies. The data analysis method used is multiple linear regression analysis of panel data processed with the Eviews program. Based on the results of data analysis, it shows that the number of audit committees affects profit management, the characteristics of the president director which include age, gender, and tenure of the president director do not affect the profit management of affiliated companies in the manufacturing sector listed on the IDX 2019-2021.